SISTEM PENUNJANG KEPUTUSAN CALON DESA PENERIMA AIR BERSIH DI KECAMATAN SUMBERLAWANG SRAGEN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Novianto Tri Sasongko; Sri Tomo; Sri Hariyati Fitriasih (STMIK Sinar Nusantara, 2018)
The purpose of this study is to make a decision support system that makes it easier for Sumberlawang District in terms of determining candidate villages receiving clean water in the area. So that the determination of distribution becomes faster and precise. The system built by the author uses a decision support method that is Simple Additive Weighting (SAW). In performing attribute selection, the author uses 4 criteria in determining the selection of water recipient village candidates. The programming language of the author uses the programming language HyperText Preprocessor (PHP). The software that supports in making applications that Macromedia Dreamweaver, Mysql, and Adobe Photoshop. The author in terms of performing performance calculations of the system using Blackbox method by applying the method, then the performance of the application built by the author has a system performance level of 100%. The result of the use of SAW method is the creation of a Decision Supporting System Support System for Water Recipient Village in Sumberlawang Sragen Using Simple Additive Weighting Method which is very helpful to Sumberlawang Sub-District in Determination of Potential of Recipient of Clean Water.Keywords: Decision Support System, SAW Method, Water Distributor.